Outcome for biliary atresia patients treated at a low-volume centre. (3rd April 2018) - Bjørnland, Kristin; Hinna, Maren; Aksnes, Gunnar; Stensrud, Kjetil Juul; Ertresvåg, Kjetil; Bjørnstad-Østensen, Anniken; Sanengen, Truls; Line, Pål-Dag; Aagenæs, Ingegerd; Aabakken, Lars; Emblem, Ragnhild; Almaas, Runar
Abstract: Objectives: The importance of case load for treatment of extrahepatic biliary atresia (BA) is debated. The aim of this study was to register results of BA treatment in a small volume centre. Methods : Retrospective chart review study of patients with BA treated from 2000 to 2017. The institutional review board approved the study. Results: Forty-five babies were identified of which 42 (93%) are alive. Forty-one patients had a Kasai portoenterostomy (PE), two had a hepaticojejunostomy and two had a primary liver transplantation. The age at PE/hepaticojejunostomy was median 63 (4–145 days). Seven surgeons performed the operations, and the median duration of the diagnostic work-up was 8 (3–24) days. Clearance of jaundice was achieved in 23/43 (53%) babies, and 3- and 5-year native liver survival was 47% and 40%, respectively. Clearance of jaundice post-PE/hepaticojejunostomy was a strong predictor of native liver survival (adjusted OR: 0.027; 95%; p = .009). Plasma level of conjugated bilirubin at time of referral was also a significant predictor of native liver survival (adjusted OR: 1.053; p = .017). Conclusion: A small volume centre may achieve satisfactory results for BA patients. The study has, however, identified factors that may further improve results; earlier referral, optimizing diagnostic work-up and establishing one dedicated surgical team.